Analisis Model Pembelajaran Discover Learning dengan Media Pembelajaran Materi Pendidikan Biologi Tingkat SMA Kabupaten Luwu - Asri; Khaerati; Olivia, Putri (Jurnal Biogenerasi, 2025)
The purpose of this study was to determine the learning outcomes of using the discovery learning model with learning media for biology, where students experienced some difficulty understanding the material. This experimental study employed an action method, namely: test instrument design, media devices, assessment sheets, and a purposive sampling technique, which involved directly selecting 32 students from the experimental class. Descriptive statistical analysis of learning outcome data revealed an average pretest learning outcome score of 36.24, categorized as low ability in the class, and an average posttest learning outcome score of 88.38, categorized as very high ability in the class. Data from the experimental class' learning management actions using the discovery learning model with learning media revealed an average reviewer assessment of the first action of 3.46, categorized as partially implemented, and the second action of 3.76, categorized as fully implemented. It was concluded that learning using the Discovery Learning model with learning media can improve learning outcomes in the first action of the low ability category and the second action of the very high ability category. Learning management actions for the first meeting were partially implemented, and for the second meeting were fully implemented.